Inflammation and Cancer: From the Development of Personalized Indicators to Novel Therapeutic Strategies - Ballerini, Patrizia; Contursi, Annalisa; Bruno, Annalisa; Mucci, Matteo; Tacconelli, Stefania; Patrignani, Paola (Frontiers in Pharmacology, 2022)
Colorectal (CRC) and hepatocellular carcinoma (HCC) are associated with chronic inflammation, which plays a role in tumor development and malignant progression. An unmet medical need in these settings is the availability of sensitive and specific noninvasive biomarkers. Their use will allow surveillance of high-risk populations, early detection, and monitoring of disease progression. Moreover, the characterization of specific fingerprints of patients with nonalcoholic fatty liver diseases (NAFLD) without or with nonalcoholic steatohepatitis (NASH) at the early stages of liver fibrosis is necessary. Some lines of evidence show the contribution of platelets to intestinal and liver inflammation. Thus, low-dose Aspirin, an antiplatelet agent, reduces CRC and liver cancer incidence and mortality. Aspirin also produces antifibrotic effects in NAFLD. Activated platelets can trigger chronic inflammation and tissue fibrosis via the release of soluble mediators, such as thromboxane (TX) A2 and tumor growth factor (TGF)-, and vesicles containing genetic material (including microRNA). These platelet-derived products contribute to cyclooxygenase (COX)-2 expression and prostaglandin (PG)E2 biosynthesis by tumor microenvironment cells, such as immune and endothelial cells and fibroblasts, alongside cancer cells. Enhanced COX-2-dependent PGE2 plays a crucial role in chronic inflammation and promotes tumor progression, angiogenesis, and metastasis. Antiplatelet agents can indirectly prevent the induction of COX-2 in target cells by inhibiting platelet activation. Differently, selective COX-2 inhibitors(coxibs) block the activity of COX-2 expressed in the tumor microenvironment and cancer cells. However, coxib chemopreventive effects are hampered by the interference with cardiovascular homeostasis via the coincident inhibition of vascular COX-2-dependent prostacyclin biosynthesis, resulting in enhanced risk of atherothrombosis. A strategy to improve anti-inflammatory agents' use in cancer prevention could be to develop tissue-specific drug delivery systems. Platelet ability to interact with tumor cells and transfer their molecular cargo can be employed to design platelet-mediated drug delivery systems to enhance the efficacy and reduce toxicity associated with anti-inflammatory agents in these settings. Another peculiarity of platelets is their capability to uptake proteins and transcripts from the circulation. Thus, cancer patient platelets show specific proteomic and transcriptomic expression profiles that could be used as biomarkers for early cancer detection and disease monitoring.